Histological Features of the Atrioventricular Conduction System in Cats with High-Grade Atrioventricular Block. (January 2022) - Machida, Noboru; Sasaki, Takafumi; Kimura, Yusuke
Summary: The histopathological features of the atrioventricular (AV) conduction system of nine cats with high-grade atrioventricular block (H-AVB) were compared with those of 22 cases of third-degree atrioventricular block (3-AVB). All nine H-AVB cats had experienced syncopal attacks of variable severity and had been diagnosed electrocardiographically. The AVB, which was permanent in all cases, had been observed for 15–1, 981 days (average 663 days) before death. Histological examination of the AV conduction system revealed moderate (25–50%) or severe (>50%) loss of conduction fibres associated with fibrous replacement in the regions of the branching portion of the AV bundle and the upper portion of the left bundle branch in almost all of the H-AVB cases and in all the 3-AVB cases. Comparison of lesion severity in each region in the H-AVB and 3-AVB cases revealed that the branching portion of the AV bundle was less severely affected in the H-AVB cases. This finding might explain why the H-AVB cases had intermittent block of AV conduction while the 3-AVB cats had permanent block.